Welcome 2 America [compact disc] - Prince (The Prince Estate/NPG Records, 2021)
Recorded in the spring of 2010 and then mysteriously abandoned by Prince before its release, the statement album documents Prince's concerns, hopes, and visions for a shifting society, presciently foreshadowing an era of political division, disinformation, and a renewed fight for racial justice.